Kinetic Model of Chemical Organic Matter Removal in Facultative Pond Set A in Domestic Wastewater Treatment Plant (WWTP) Bojongsoang, West Java - Novia, Fanny; Herliana, Erika; Saepurohman, Jeni (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Kinetic models are widely used to predict the performance of biological treatment systems. The facultative ponds are applied as a biological treatment for domestic wastewater in the Wastewater Treatment Plant (WWTP) located in Bojongsoang, Bandung Regency, West Java. This study aims to evaluate the suitability of several kinetic models for the chemical oxygen demand (COD) removal process that occurs in facultative ponds in WWTP Bojongsoang. The best kinetic model will provide a more accurate predictions of COD effluent concentrations in facultative ponds. Data series of COD influent and effluent concentration were collected from field data of water quality monitoring monthly from years 2019 to 2022. The kinetic models used in this study were the first-order kinetic model combined plug flow pattern, the first-order kinetic model with continuous stirred tanked reactor flow pattern, the plug flow k-C* model, and the Stover-Kincannon model. Model accuracy was evaluated using statistical methods by calculating the mean average percentage error (MAPE) to compare model data with measured observation data. The COD effluent prediction showed that the Plug Flow k-C* model had the smallest MAPE for both facultative ponds, namely 28.3% for facultative pond 1A and 30.2% for facultative pond 2A. Kinetic rate values for both facultative ponds using plug flow k-C* model respectively, 0.1818 m/day for F1A and 0.1750 m/day for F2A.